Synaptic properties of the feedback connections from the thalamic reticular nucleus to the dorsal lateral geniculate nucleus - Campbell, Peter W. (J Neurophysiol, 2020)
The thalamic reticular nucleus (TRN) is a shell-like structure comprised of GABAergic neurons that surrounds the dorsal thalamus. While playing a key role in modulating thalamocortical interactions, TRN inhibition of thalamic activity is often thought of as having an all-or-none impact. Although TRN neurons have a dynamic firing range, it remains unclear how variable rates of TRN activity gate thalamocortical transmission. To address this, we examined the ultrastructural features and functional synaptic properties of the feedback connections in the mouse thalamus between TRN and the dorsal lateral geniculate nucleus (dLGN), the principal relay of retinal signals to visual cortex. Using electron microscopy to identify TRN input to dLGN, we found that TRN terminals formed synapses with non-GABAergic postsynaptic profiles. Compared with other nonretinal terminals in dLGN, those from TRN were relatively large and tended to contact proximal regions of relay cell dendrites. To evoke TRN activity in dLGN, we adopted an optogenetic approach by expressing ChR2, or a variant (ChIEF) in TRN terminals. Both in vitro and in vivo recordings revealed that repetitive stimulation of TRN terminals led to a frequency-dependent inhibition of dLGN activity, with higher rates of stimulation resulting in increasing levels of membrane hyperpolarization and corresponding decreases in spike firing. This relationship suggests that alterations in TRN activity lead to graded changes in relay cell spike firing. NEW & NOTEWORTHY The thalamic reticular nucleus (TRN) modulates thalamocortical transmission through inhibition. In mouse, TRN terminals in the dorsal lateral geniculate nucleus (dLGN) form synapses with relay neurons but not interneurons. Stimulation of TRN terminals in dLGN leads to a frequency-dependent form of inhibition, with higher rates of stimulation leading to a greater suppression of spike firing. Thus, TRN inhibition appears more dynamic than previously recognized, having a graded rather than an all-or-none impact on thalamocortical transmission.